Same-Sex Families and Legal Recognition in Europe - Digoix, Marie (European Studies of Population, 2020)
This open access book focuses on family diversity from a legal, demographical and sociological perspective. It investigates what is at stake in the life of homosexuals in the field of family formation, parenting and parenthood, what it brings to everyday life, the support of the law, and what its absence implies. The book shows the paths leading to the adoption of laws while demographic analyses concentrate on the link between registration of same-sex marriages and same-sex parenting with a detailed focus on Spain. The sociological chapters in this book, based upon qualitative surveys in France, Iceland and Italy, underline how the importance of the legal structure influenced the daily life of homosexual families. As such this book is an interesting read to lawyers, demographers, sociologists, behavioural scientists, and all those working in the field.